Penerapan Metode Profile Matching pada Penilaian Kinerja Dosen - Effendy, Geraldo Revanska; Yuhandri, Yuhandri; Sovia, Rini (Jurnal PROCESSOR, 2025)
The evaluation of lecturer performance at Adzkia University faces challenges in terms of inefficient data processing. This research aims to implement the Profile Matching method to optimize the lecturer performance assessment system, evaluate its effectiveness, and develop an application based on this method. The research was conducted using a quantitative method employing Profile Matching, which includes several stages: GAP calculation, GAP mapping, core factor and secondary factor analysis, total value calculation, and ranking determination. The evaluation was conducted on 38 lecturers considering five main criteria: Adzkian Values, Education, Research, Community Service, and Supporting Activities, which are detailed in 28 sub-criteria. The implementation of the Profile Matching method proved to produce objective assessments by placing Lecturer 31 as the lecturer with the highest score (4.251), followed by Lecturer 3 and Lecturer 30 (4.092). The developed web-based application successfully integrated this method and improved the efficiency of the assessment process. This study demonstrates the effectiveness of the Profile Matching method in evaluating lecturer performance with more objective results. The implemented system helps BPSDM conduct assessments more efficiently and generate more structured reports.